Learning Motivation increased due to a Relaxed Assessment in a Competitivee-Learning Environment - Muhammad Said Hasibuan; Onno W Purbo (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
In this work, e-learning is used to increase learners 'motivation and competence in addition to learning complementary environment. This work is based on of the 7-years of hybrid e-learning classes on Operating System, Computer Network, Network Security, Network Management subjects at 3 Indonesian universities, namely, Surya University, STKIP Surya, and IBI Darmajaya. Most of STKIP Surya's students are from Papua and need more attention and motivation than others. Relaxed assessment processes are performed on each module in addition to mid term and final exams. On average, there are 12-18 modules in each subject matter. To motivate the learners, they may perform as many exams as ones' wish to attained the highest possible mark within the semester on all exams and quizzes. Relaxed assessment processes to attained maximum grades seems to increase the learners' motivation as some learners' retrying in exceeding 50 times for the 100 questions final shown in the Level of Competency (LoC) measurement. In addition, to anticipate, any cheating, eliminate remedial and cost savings, all exams are done on moodle via web. Such method of a whole semester relaxed assessment equipped with about 2000-6000 questions bank per subject and is for the first time performed in Indonesia. This study is also found an increase in the majority of learner's understanding on the subject is very good without remedial. Thus, e-learning seems not only complement learning processes but also able to motivate and to improve the competence of learners as well creating healthy competitive environment among learners.